Peningkatan Efektivitas Operasional Melalui Implementasi ITIL V3 Pada Sistem Informasi“New Modern” Dengan Fokus Service Operation (Studi Kasus: CV Cahaya Makmur Abadi) - Tarwoto; Selina Isni Setiasih; Ragilah Ismiyati; Afilda Trisetya Riziana; Uthana Kalyana Mitha; Devi Yunita Saputri (NUANSA INFORMATIKA, 2024)
Cv Cahaya Makmur Abadi is a modern cotton distributor company located in Banyumas. Currently, Cv Cahaya Makmur Abadi is facing several operational issues in using the New Modern system. To enhance operational effectiveness, this research implements the ITIL V3 framework, particularly in the service operation domain, which includes Event Management, Incident Management, Problem Management, Request Fulfillment, and Access Management. It is expected that through the implementation of ITIL V3, the issues faced by Cv Cahaya Makmur Abadi can be minimized, and the company's operations can run more efficiently and effectively. In addressing the challenges encountered during the operation of the New Modern System at Cv Cahaya Makmur Abadi, the author recommends the use of the ITIL V3 approach in the Service Operation section. ITIL V3 is a framework that can help improve the operational effectiveness of information systems. Although an analysis has been conducted, there are still some areas within the Service Operation domain that need improvement.